Penerapan Metode Case Based Reasoning untuk Diagnosa Penyakit Kulit Akibat Virus Eksamtema Berbasis Web - Anggriani Eti Bulu; Andreas Ariyanto Rangga; Maria Wilda Malo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Currently, patients experiencing early symptoms of skin disease caused by the exanthema virus are unable to immediately consult a dermatologist due to the high cost and limited time available for specialists in hospitals. Therefore, the author needs to develop an expert system application that can address this issue. Through this application, users can consult with the system, much like an expert, to diagnose their symptoms and find solutions to their problems. This expert system is designed to provide answers based on whether the symptoms are correct or not, or to provide several recommended answer choices based on the symptoms. To diagnose skin disease caused by the exanthema virus, the author used the Case-Based Reasoning method. The CBR method is a weighting technique that compares new cases with previous cases. The diagnosis is based on data provided by the patient and expert, which is then analyzed using case-based reasoning and stored as a knowledge database in the expert system. Therefore, this expert system can help identify solutions for problems experienced by patients suffering from skin disease caused by the Exanthema Virus.